Applications of Number Theory to Cryptography: A Look Into the Diffie-Hellman Key Exchange and the RSA Cipher - Suraj Oruganti (International Journal of Mathematics And its Applications, 2020)
Number theory is the study of integer values, and as Carl Friedrich Gauss once coined it, "the queen of mathematics." More specifically, a field of study in number theory is the behavior of prime numbers. Cryptography is the development of algorithms in order to transmit information securely. Number Theory is intertwined with, and is an integral part of cryptography. Therefore, in this paper we will be discussing the applications of number theory to cryptography.